PARTICIPATION OF SANGHA IN PUBLIC WELFARE: CASE STUDY OF THE DHAMMAYUTTIKA SANGHA, NONSILA DISTRICT, KHONKAEN PROVINCE - Chavano, Phrakru Chaiwatphisan; ., Phrakru Wootidhamsal (Journal of MCU Nakhondhat, 2024)
This research aims to study the concept of the theory of the participation of the Sangha in public welfare, study the public welfare work of the Thammayut Nikaya Sect, and analyze the participation of the Thammayut Nikaya Sect in public welfare in Non Sila District, Khon Kaen Province. This is a qualitative research, collecting data from documents, textbooks, books, and related research. The research results found that participation in public welfare is a way to strengthen the power of working together according to the theory of Cohen and Uphoff, which consists of 4 aspects: 1) Participation in decision-making, 2) Participation in operations, 3) Participation in benefits, and 4) Participation in evaluation. The public welfare work of the Thammayut Sangha is an operation to provide welfare according to the regulations of the Thai Sangha, which consists of 4 aspects: 1) Conducting activities to help and support, 2) Supporting the activities of others for public benefit, 3) Supporting public property, and 4) Supporting the general public. And the analysis of the participation of the Sangha in public welfare has 4 aspects: 1) The Sangha participates in activities to help and support by organizing a project to save lives of cows and buffaloes. 2) The Sangha participates in helping others' activities for public benefit by organizing a project to provide scholarships and educational equipment to students. 3) The Sangha participates in helping public property by organizing a project to build a bell tower at Wat Pa Thammarangsri. 4) The Sangha participates in helping people by organizing a project to help disaster victims.